DOES INNOVATION CAPABILITY AND TECHNOLOGY CAPABILITIES AFFECT THE MARKETING PERFORMANCE OF SMES IN INDONESIA? - Bintoro Bagus Purmono (Jurnal Ekonomi, 2023)
Small and Medium Enterprises (SMEs) in Indonesia are the backbone of the national economy. The number is expected to continue to increase to have an existence with sustainable competitiveness. The competitiveness of SMEs will become a necessity if SMEs are an essential element in maintaining a competitive position. Innovation capability and Technology capabilities are crucial elements in creating sustainable competitiveness. Profit-maximizing activities also determine the survival of SME businesses through a market-oriented approach to dealing with marketing challenges. Marketing performance is the key to business success due to market strategies for customers, markets, and financial organizations. Marketing performance focuses on sales growth, market share, and market development in marketing performance studies. This research will examine how much innovation and technology capabilities influence marketing performance for SME activists in Indonesia. Using Structural Equation Modeling (SEM) and AMOS statistical tools, this study examined the relationship between the independent variables and the dependent variable to support the developed hypothesis. Methods of data collection using a questionnaire with a number of respondents 206 people. The study's findings demonstrate that capabilities in innovation and technology positively and significantly impact marketing performance. Technology capabilities also show a strong influence on innovation capability. Meanwhile, innovation capability mediates between technology capabilities and marketing performance.